Resistencia a colistín mediado por el gen mcr-1 identificado en cepas de Escherichia coli y Klebsiella pneumoniae. Primeros reportes en el Perú - Ugarte Silva, Ruth Giovanna (2018)
Introduction. Given the appearance of reports of the presence of the mcr-1 gene and its possible dissemination by plasmids in the countries of the region and given that this gene confers resistance to colistin, the drug that is the last line of treatment against multiresistant bacteria, it is important to know its presence in our country in microorganisms that express it. Methods. Descriptive and cross-sectional study was carried out. Microorganisms isolated from urine culture of outpatients from a private health center in Lima, Peru, were included in august 2017. Out of 326 positive urine cultures, 10 isolates were selected between strains of Escherichia coli and Klebsiella pneumoniae that had a minimum inhibitory concentration ≥4μg/mL (interpreted as resistant for colistín) by the automated system Microscan Walkaway 96 plus. The following methods were used: colistin agar spot, prediffusion with colistin tablets, microdilution in colistin broth and PCR for the mcr-1 gene. Results. It was determined that 7 isolates, all Escherichia coli, expressed the presence of the mcr-1 gene by PCR, which confers plasmid resistance to polypeptides. Of the remaining strains, two Escherichia coli and one Klebsiella pneumoniae, were positive for resistance to colistin in the phenotypic tests but not in the PCR for mcr-1 gene, which suggests a mechanism of colistin resistance not associated with the mcr-1 gene. Conclusions. Seven isolates of Escherichia coli resistant to colistin and with expression of the mcr-1 gene were obtained.